NEW FINANCIAL TECHNOLOGIES CHANGE OUR WORLD - V. V. Maslennikov; M. A. Fedotova; A. N. Sorokin (Финансы: теория и практика, 2017)
The article describes the main trends in the development of new financial technologies (Fintech), identifies the reasons for their active penetration into the financial services sector , industry and governmental organizations . It provides a detailed analysis of various forecasts for the global development of Fintech , including attracting investment . The main Fintech components have been considered in this research: blockchain, cryptocurrency , digital money, neobanks and cyber security. The analysis of the world practice of Fintech regulation and standardization has been carried out. Special attention has been given to the issues related to the position of the Bank of Russia on new digital services; the importance of the blockchain technology in government and economy has been emphasised. The article reveals a new approach to the concept of “money” and describes a new level of financial technologies using virtual banks . The paper mentions relevant issues of cyber security development for the national payment system. The constraints faced by the development of financial technologies both globally and in Russia have been revealed. The authors show possible ways to overcome such constraints by means of training new financial and information technology specialists by leading universities. The objective of this research is to discover reasons for the rapid Fintech development under modern conditions: the area of its application ; the main problems and limitations arising from the actual use of new financial technologies in the Russian Federation. The article proves that the development of Fintech will require a fundamental change in the competencies of specialists in the field of finance, banks and business.